2009
DOI: 10.1111/j.1476-5381.2009.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nitric oxide‐activated guanylyl cyclase by calmodulin antagonists

Abstract: Background and purpose: Nitric oxide (NO) controls numerous physiological processes by activation of its receptor, guanylyl cyclase (sGC), leading to the accumulation of 3′-5′ cyclic guanosine monophosphate (cGMP). Ca 2+ -calmodulin (CaM) regulates both NO synthesis by NO synthase and cGMP hydrolysis by phosphodiesterase-1. We report that, unexpectedly, the CaM antagonists, calmidazolium, phenoxybenzamine and trifluoperazine, also inhibited cGMP accumulation in cerebellar cells evoked by an exogenous NO donor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…CyaA and sarcoplasmatic/endoplasmatic reticulum Ca 2+ -ATPase (SERCA)), where CDZ acts as a potent inhibitor, it was suggested that the potency of inhibition is correlated with the hydrophobicity and the size of the inhibitor [ 21 , 49 ]. In contrast to most of above CaM-inhibitors, CDZ inhibits many CaM-targets in a CaM-independent manner [ 18 , 21 , 49 52 ]. Table 1 summarizes the effects of CaM-inhibitors on CaM-target interactions.…”
Section: Introductionmentioning
confidence: 99%
“…CyaA and sarcoplasmatic/endoplasmatic reticulum Ca 2+ -ATPase (SERCA)), where CDZ acts as a potent inhibitor, it was suggested that the potency of inhibition is correlated with the hydrophobicity and the size of the inhibitor [ 21 , 49 ]. In contrast to most of above CaM-inhibitors, CDZ inhibits many CaM-targets in a CaM-independent manner [ 18 , 21 , 49 52 ]. Table 1 summarizes the effects of CaM-inhibitors on CaM-target interactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, we detected no manipulation of AMPylation by any of the tested compounds relative to the DMSO control ( Figure S5 ). The activity of calmidazolium against HYPE and VopS is likely attributable to its vast biological promiscuity, rather than some Fic-specific mechanism [ 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both CALMID and TFP were previously shown to inhibit CaM activity primarily by binding directly to the protein (Matsushima et al, 2000;Sunagawa et al, 2000). However, CALMID and TFP probably exert many of their actions not only via their binding to CaM, but also by interfering directly with a number of upstream (Qin et al, 2009) or downstream targets of CaM signaling (James et al, 2009;Sunagawa et al, 2000). For example, the Rho family GTPases, e.g.…”
Section: Discussionmentioning
confidence: 99%